Grounding psychological help for adolescents with atopic dermatitis - O. Uskov; M. Markova (Kazimierz Wielki University, 2015)
Uskov O., Markova M. Grounding psychological help for adolescents with atopic dermatitis. Journal of Education, Health and Sport. 2015;5(5):138-150. ISSN 2391-8306. DOI 10.5281/zenodo.17465 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A138-150 https://pbn.nauka.gov.pl/works/559212 http://dx.doi.org/10.5281/zenodo.17465 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015.   UDC 616.89: 616.5-009   GROUNDING psychological help for adolescents with atopic dermatitis   O. Uskov, M. Markova   Kharkiv Medical Academy of Post-graduate Education   Abstract. The article addresses some information about psychological problems, emotional state, personal, behavioral and family-associated patterns in adolescents with atopic dermatitis, which served a basis for differentiation of targets and measures of psychological help. There were defined such targets of psychological interventions as follows: physical discomfort, self-perception of the appearance, poor therapy compliance, reduced mental activity, high levels of anxiety, depressive manifestations, disharmonious personal features, a destabilizing profile of coping strategies, distancing and avoidance strategies, problems in child-parent relationships, imbalanced marital relationships, affected self-acceptance, imbalanced in the internality-externality axis, high escapism. As psychological interventions there were used some techniques of Gestalt therapy, rational therapy, art therapy, cognitive-behavioral therapy, psychological training. Family therapy was an important component of psychological help for adolescents with atopic dermatitis. Key words: atopic dermatitis, adolescents, psychological help.